The Effect of Vitamin D3 on Neutrophil Extracellular Trap Formation in High-Glucose Conditions - Basyreva, L. Yu; Shmeleva, E. V.; Ivanov, V. A.; Vakhrusheva, T. V.; Panasenko, O. M.; Ostrovsky, E. M.; Gusev, S. A.; Sergienko, V. I. (Bulletin of experimental biology and medicine, 2023)
NETosis, i.e ., the formation of neutrophil extracellular traps (NET), and neutrophil autophagy are important elements in the pathogenesis and the development of complications of type 2 diabetes mellitus (T2DM). Therefore, the search of drugs that can regulate the level of NETosis and autophagy in T2DM is relevant. Here we studied an ex vivo NET formation and neutrophil death in whole blood from healthy subjects upon the addition of glucose up to a high concentration of 15 mM or/and the phorbol ester PMA (phorbol-12-myristate-13-acetate). Their individual and combined action caused neutrophil death and an increase in NET content. It can be hypothesized that this resulted from activation of NETosis and autophagy. It was also shown that this activation of NETosis and autophagy is completely prevented by daily intake of 1000 IU vitamin D3 for 14 days. Therefore, vitamin D3 supplementation can be considered as a preventive measure against the development of T2DM complications.